Visual Search Image Recognition Marketing Mechanism, Short-Form Ephemeral Content Marketing Mechanism on the Sales of Graphic Artworks in Calabar Metropolis, Nigeria - Etoma, Moses George; Adie, Anthonia Ugiebeme (The Indonesian Institute of Science and Technology Research, 2025)
This study examined the influence of visual image recognition marketing and short-form ephemeral content marketing on the sales of graphic artworks in Calabar Metropolis. Guided by two research questions and two null hypotheses, the study adopted a descriptive survey research design. The population comprised graphic artists, digital content creators, art dealers, gallery owners, social media marketers, and buyers of graphic artworks, from which 100 participants were purposively selected. Data were collected using a validated structured questionnaire and supplemented with semi-structured interviews. Reliability of the instrument was confirmed with a Cronbach’s Alpha coefficient of 0.70. Data analysis employed descriptive statistics (means, frequencies, and percentages) and inferential statistics, including Pearson’s correlation and regression analysis, while qualitative data were analyzed thematically. Findings revealed that visual image recognition marketing significantly influences sales of graphic artworks (r = 0.52, p < 0.05), accounting for 27% of sales variation. Similarly, short-form ephemeral marketing significantly influences sales (r = 0.55, p < 0.05), accounting for 30% of sales variation. Both strategies were found to enhance brand visibility, consumer engagement, and purchase intention, although some respondents noted potential drawbacks such as reduced audience retention or discoverability issues. The study concluded that integrating compelling, high-quality visuals with timely, short-form promotional content can substantially improve sales performance in the creative arts sector. It was recommended that artists and marketers invest in consistent visual branding, leverage social media short-form formats, and adopt analytics tools to monitor and optimize marketing impact.